GEOMETRI JALAN ANGKUT DAN JARI-JARI TIKUNGAN MENGGUNAKAN TEORI AASHTO PADA PT PRO INTERTECH INDONESIA KOTA SORONG PROVINSI PAPUA BARAT - Hamdan Tri Sanjaya; Ricardo O. M. Hutapea (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
Hauling road is an important aspect to support hauling activities in a mining operation. Better hauling road conditions will optimalize production, where is consistent with production plans and targets. The calculation of road conditions should be adjusted to the needs. The road geometry is a part of road planning which focuses on the physical condition of the road so that it can fulfill the road function. In addition to the geometry of the hauling roads, water can also affect the condition of the hauling roads. Therefore, it is important to conduct an evaluation of the hauling road conditions. Based on the calculation results, the straight road width is 8,575 meters, the hauling road width at the bend is 19,356 meters, while the straight road width in the field is about 7.6 meters and for curves in the field about 9 meters. From the field processed data, it is indicated that the existing hauling roads at PT Pro Intertech Indonesia mining operation has not fully met the hauling road requirements. Therefore, it is necessary to widen the hauling road in the operation area.